The usage of Islamic banking products among customers at Bank Rakyat Jalan Hang Tuah Melaka / Muhammad Sufian Mohd - Mohd, Muhammad Sufian (Faculty of Business and Management, 2015)
Islamic banking system as a new banking structure has drastically increased its operations in order to expand its usage in different part of the world. The main objective of the study is to identify the factors that influencing the usage of Islamic banking products. A structural questionnaire is constructed to collect data to answer the research questions as being framed on related affective factors that influence consumers’ preference towards Islamic banking services in Malaysia. In this study, we have frequency testing, descriptive analysis, correlation and regression analysis. The results show that all the independent variabes which are social influences, high profit rates, good quality of services and strict compliant to shariah principle show the significant and positive relationship with the usage of Islamic banking products. One potential limitation of this study is less cooperation from respondent to answer the questionnaires appropriately. Therefore, a generalization about the entire population of Malaysian banking customers of banking sector is inappropriate. The findings of the study can facilitate the Islamic banking service providers to introduce innovative service offering in according to Islamic shariah principle. It can be concluded all the independent variables can be accepted.